Customer satisfaction in catering industry: Contrasts between Lithuania and Portugal - Pileliene,Lina (2016)
This paper analyzes the differences among customer satisfaction in catering industry in two different countries: Lithuania and Portugal. The adjusted European Customer Satisfaction Index is applied for the measurement of the customer satisfaction in the catering industry. The data are collected in 2014, with the aim to identify the key factors that could affect the customer satisfaction in the catering industries in these two countries. The results indicated that the determinants of customer satisfaction with catering facilities are quite similar in both countries. Eight structural relations are significant: image influences expectations and loyalty; expectations influence perceived quality; perceived quality influences perceived value and satisfaction; perceived value influences satisfaction; and satisfaction influences loyalty and complaints. Three statistically non-significant direct causal relations are the same: complaints do not influence loyalty; expectations do not influence perceived value as well as satisfaction. Only one country-specific relation is detected: the effect of image on satisfaction is statistically significant only for Portuguese consumers.